Event-related changes in neuromagnetic activity associated with syncopation and synchronization timing tasks - Mayville, Justine M.; Fuchs, Armin; Ding, Mingzhou; Cheyne, Douglas; Deecke, Lüder; Kelso, J.A. Scott (Human brain mapping, 2001)
For low rhythmic rates (1.0 to ∼2.0 Hz), subjects are able to successfully coordinate finger flexion with an external metronome in either a syncopated (between the beats) or synchronized (on each beat) fashion. Beyond this rate, however, syncopation becomes unstable and subjects spontaneously switch to synchronization to maintain a 1:1 stimulus/response relationship. We used a whole‐head magnetometer to investigate the spatiotemporal dynamics of neuromagnetic activity (MEG) associated with both coordinative patterns at eight different rates spanning the range 1.0–2.75 Hz. Timing changes in the event‐related fields accompanied transitions from syncopation to synchronization and followed the placement of the motor response within each stimulus/response cycle. Decomposition of event‐related fields into component auditory and motor brain responses revealed that the amplitude of the former decreased with increasing coordination rate whereas the motor contribution remained approximately constant across all rates. Such an interaction may contribute to changes in auditory‐motor integration that cause syncopation to become unstable. Examination of event‐related changes in high frequency bands revealed that MEG signal power in the beta band (15–30 Hz) was significantly lower during syncopated coordination in sensors covering the contralateral sensorimotor area suggesting a dependence of beta rhythm amplitude on task difficulty. Suppression of beta rhythms was also stronger during synchronization preceded by syncopation, e.g., after subjects had switched, when compared with a control condition in which subjects synchronized throughout the entire range of rates. Hum. Brain Mapping 14:65–80, 2001. © 2001 Wiley‐Liss, Inc.